Africa, the Cradle of Human Diversity Cultural and Biological Approaches to Uncover African Diversity - Fortes-Lima, Cesar; Mtetwa, Ezekia; Schlebusch, Carina (Africa-Europe Group for Interdisciplinary Studies, 2022)
This book brings together experts from several disciplines, reviewing and discussing our current knowledge of the complex history, biological diversity and behavioral evolution of African populations. The collection provides a valuable resource for students and researchers from various fields.; Readership: This book offers accessible knowledge from a multidisciplinary perspective to students, scholars and researchers interested in human evolutionary history, population genetics, archaeology, paleogenomics, anthropology, and related disciplines.